Tanggung Jawab Gereja Membangun Eco-Tourism Pendidikan-Ekonomi Jemaat Di Daerah Sumatera Utara - Pinondang J. Simanjuntak (Jurnal Magistra, 2023)
The church is a religious institution that has an important role in community development, including the economic development of the congregation. One form of congregational economic development that can be carried out by the church is through the development of eco-tourism. Eco-tourism is a form of tourism that prioritizes ecological and educational aspects. By developing eco-tourism, churches can provide education to the public about the importance of preserving nature, as well as improving the economic welfare of the congregation. This is based on the church's call to be salt and light in the world, and to improve the welfare of the congregation. Educational eco-tourism can be used as a means to realize this call. Educational eco-tourism is a tourism activity that focuses on environmental conservation and education. This activity can provide benefits for the environment, economy and education.